Tucatinib with capecitabine and trastuzumab in advanced HER2-positive metastatic breast cancer with and without brain metastases: a non-randomised, open-label, phase 1b study. Issue 7 (July 2018) - Murthy, Rashmi; Borges, Virginia F; Conlin, Alison; Chaves, Jorge; Chamberlain, Marc; Gray, Todd; Vo, Alex; Hamilton, Erika
Summary: Background: Tucatinib is a potent and selective oral HER2 tyrosine kinase inhibitor, with the potential to provide a well tolerated new treatment option for patients whose disease has progressed on currently available therapies. We aimed to determine the recommended phase 2 dose, safety, pharmacokinetics, and preliminary activity of tucatinib in combination with capecitabine or trastuzumab in patients with HER2-positive breast cancer with or without brain metastases. Methods: In this non-randomised, open-label, phase 1b trial done in five sites in the USA, we recruited patients aged 18 years or older with HER2-positive progressive breast cancer who had been previously treated with trastuzumab, pertuzumab, and trastuzumab emtansine. Eligible patients required HER2-positivity assessed locally, evaluable lesions as defined per Response Evaluation Criteria in Solid Tumors, version 1.1, and an Eastern Cooperative Oncology Group performance status of 0 or 1. Tucatinib was administered twice a day in conjunction with capecitabine 1000 mg/m 2 orally twice a day for 14 days of a 21-day cycle, trastuzumab 6 mg/kg intravenously once every 21 days, or both. A modified 3 + 3 dose-escalation design was used to determine the recommended phase 2 dose, starting with tucatinib in combination with capecitabine or trastuzumab, and subsequently evaluating the triplet combination. The primary endpoint was to establish the maximum tolerated dose and recommended phase 2 dose of tucatinib, evaluated by toxicity assessments. Efficacy was assessed in all patients by contrast CT of the body. Analyses included all patients who had received at least one dose of study treatment. The study is registered withClinicalTrials.gov, numberNCT02025192 . Findings: Between Jan 15, 2014, and Dec 15, 2015, 60 patients were enrolled and treated. The current report is from mature data as of June 30, 2017. The tucatinib recommended phase 2 dose was determined to be 300 mg orally twice a day, equivalent to single-agent maximum tolerated dose. Pharmacokinetic analysis showed that there was no drug–drug interaction with capecitabine. Adverse events seen at the recommended phase 2 dose regardless of causality, grade, and treatment group included diarrhoea (35 [67%] of 52 patients), nausea (31 [60%] patients), palmar-plantar erythrodysaesthesia syndrome (23 [44%] patients), fatigue (20 [38%] patients), and vomiting (20 [38%] patients). In all patients, treatment-related toxicities of grade 3 and worse included fatigue (five [8%] patients), diarrhoea (four [7%] patients), and palmar-plantar erythrodysaesthesia (four [7%] patients). No treatment-related deaths were reported. The proportion of patients with measurable disease achieving objective response was 83% (five of six patients) in the combination of tucatinib with capecitabine, 40% (six of 15 patients) in the combination of tucatinib with trastuzumab, and 61% (14 of 23 patients) in the combination of tucatinib with both capecitabine and trastuzumab. Interpretation: Tucatinib in combination with capecitabine and trastuzumab had acceptable toxicity and showed preliminary anti-tumour activity. Validation of the current study results will be determined in the double-blinded randomised study, HER2CLIMB (ONT-380-206;NCT02614794 ). Funding: Cascadian Therapeutics, a wholly owned subsidiary of Seattle Genetics.